Genealogia międzynarodowości. Społeczna teoria stosunków międzynarodowych - GAŁGANEK, Andrzej (Przegląd Politologiczny, 2018)
In several papers recently published by the author, the main reference was the theoretical considerations of Justin Rosenberg, in an attempt to show the reasons for the dichotomization of ‘internationality’ and ‘internality,’ and the ways of overcoming this dichotomization. This paper attempts to resolve and conclude these previously discussed issues. On the ground of Rosenberg’s theoretical assumptions, the paper answers the questions of where ‘internationality’ originated, and what is a decisive factor for its existence as the dimension of the social world. The author makes reference to the notion of uneven and combined development as interpreted by J. Rosenberg so as to reconstruct the methods applied in answering the above questions in three stages. Firstly, he discusses the model, allowing a comparison of different methods of combining uneven development with international relations. It emerges that, thus far, all these methods have tended to assume political multiplicity (internationality) rather than explain its existence. Secondly, the author reconstructs the explanations referring to the historical-and-sociological argument presented in the work of Barry Buzan and Richard Little. They place the sources of internationality in the prehistoric transition from a hunter- gatherer existence to an agricultural one, which was connected with processes of social diversification and the formation of proto-states. At first glance, Buzan and Little’s explanation seems to make the notion of uneven and combined development redundant. On more detailed analysis, however, ‘unevenness’ and ‘combination’ turn out to play a key role in Buzan and Little’s empirical argument, albeit not theorized upon. Thirdly, the author of this paper demonstrates how ‘unevenness’ and ‘combination’ are necessary elements in processes of social transformation. Thus, he demonstrates that the sources of ‘internationality’ do come from the uneven and combined nature of historical development.